The effect of timing of thermal conditioning during incubation on embryo physiological parameters and its relationship to thermotolerance in adult broiler chickens - Moraes, VMB; Malheiros, R. D.; Bruggeman, V; Collin, A.; Tona, K.; Van As, P.; Onagbesan, O. M.; Buyse, J.; Decuypere, E.; Macari, Marcos [UNESP] (Elsevier B.V., 2004)
Previously, we reported that thermal conditioning at 39degreesC on days 13-17 of incubation of broiler eggs enabled thermotolerance during post-hatch growth (J. Therm. Biol. 28 (2003) 133). Tolerance to a temperature of 30degreesC was accompanied by changes in thyroid hormones and metabolic parameters. In the current study, we determined the mechanism of epigenetic heat adaptation during embryonic age by measuring blood physiological parameters that may be associated with the ultimate effects of thermal conditioning. Hatching eggs from Ross breeders were subjected to heat treatment of 39degreesC at days 13, 14, 15, 16 and 17 of incubation for 2 h per day. Control eggs were incubated at 37.6degreesC. Samples of eggs were withdrawn on each day of thermal conditioning and at internal pipping (IP) to obtain blood samples from embryos. The remaining eggs were weighed at day 18 and transferred to hatchers. The timing of IP, external pipping (EP) and hatching were monitored every 2 h. At hatch, chicks were weighed and hatchability was determined. Blood samples were obtained from samples of day-old chicks. T3, T4, corticosterone, pCO(2), pO(2) levels were determined in the blood. Blood pH was measured and T3/T4 ratios were calculated. Heat conditioning significantly increased corticosterone and pO(2) levels and blood pH but depressed pCO(2) at day 14. These were followed by a significant depression of T4 level on day 15. Remarkably, at day 16, all these parameters were back to normal as in the control embryos. Hatching was delayed by thermal conditioning probably as a result of the depressed corticosterone levels at IP. Hatchability was also lower in the heat-treated group but 1-day old chick weights were comparable to those of the controls. The result suggests that epigenetic thermal conditioning involves changes in these physiological parameters and probably serve as a method for epigenetic temperature adaptation since the same mechanisms are employed for coping with heat during post-embryonic growth. It also suggests that days 14-15 may be the optimal and most sensitive timing for evoking this mechanism during embryonic development. The adverse effects of heat treatment observed in this study may have been due to the continued exposure to heat until day 17. Fine-tuning thermal conditioning to days 14-15 only may improve these production parameters. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: thermal conditioning; chicken embryo; incubation; blood parameters; hatching parameters; thermotolerance; bird; gallus domesticus; heat stress; Hormones